Weight gain following treatment of hyperthyroidism-A forgotten tale - Kyriacou, Angelos; Kyriacou, Alexis; Makris, Konstantinos C.; Syed, Akheel A.; Perros, Petros (My University, 2019)
Hyperthyroidism causes weight loss in the majority, but its effect is variable and 10% of patients gain weight. Its treatment usually leads to weight gain and some studies have reported an excess weight regain. However, there is considerable inter-individual variability and a differential effect on body weight by different treatments, with some studies reporting more weight increase with radioiodine, and perhaps surgery, compared with anti-thyroid drugs. The excess weight regain may relate to treatment-induced hypothyroidism. Furthermore, the transition from hyperthyroidism to euthyroidism may unmask, or exacerbate, the predisposition that some patients have towards obesity. Other risk factors commonly implicated for such weight increase include the severity of thyrotoxicosis at presentation and underlying Graves' disease. Conflicting data exist whether lean body mass or fat mass or both are increased post-therapy and whether such increments occur concurrently or in a sequential manner; this merits clarification. In any case, clinicians need to counsel their patients regarding this issue at presentation. Limited data on the effect of dietary interventions on weight changes with treatment of hyperthyroidism are encouraging in that they cause significantly lesser weight gain compared to standard care. More research is indicated on the impact of the treatment of hyperthyroidism on various anthropometric indices and the predisposing factors for any excessive weight gain. Regarding the impact of dietary management or other weight loss interventions, there is a need for well-designed and, ideally, controlled intervention studies.
Keywords: Hyperthyroidism; Obesity; Treatment; Weight changes